2019
DOI: 10.3390/coatings9120782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mesenchymal Stem Cells and Osteoblasts’ Adhesion and Proliferation in the Presence of HA-AL Biomaterials

Abstract: There is an increased interest in developing biocomposite implants with high biocompatibility in order to be used as grafts or prostheses in orthopedic surgery. The purpose of the study was to determine the biocompatibility of titanium implants coated with synthesized hydroxyapatite-alendronate composites. The implants were obtained using Matrix Assisted Pulsed Laser Evaporation technique (MAPLE). The hydroxyapatite-alendronate composites were synthesized using the wet precipitation method. Immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…At passage 2, the cells were subjected to immunophenotyping by flow cytometry for validation of specific markers and then used in experiments or cryopreserved. For all experiments performed in the study, cells were seeded at a density of 5000 cells/cm 2 [12].…”
Section: Culture Of Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…At passage 2, the cells were subjected to immunophenotyping by flow cytometry for validation of specific markers and then used in experiments or cryopreserved. For all experiments performed in the study, cells were seeded at a density of 5000 cells/cm 2 [12].…”
Section: Culture Of Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Researchers found that the most effective treatment strategy is to use antibiotic loaded biocomposite based implants which contain the drug either attached to the surface or incorporated in bulk [13]. Synthetic polymers such as poly(-methylmethacrylate) or poly(D,Llactic-co-glycolic acid) [14] and natural polymers that include collagen, cellulose, chitosan [15] have been used either in association or not with hydroxyapatite [16,17] for the synthesis of such implants. Moreover, implants may include antibiotics such as ciprofloxacin, gentamycin, oxacillin, or vancomycin [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Local drug delivery systems, consisting of non-biodegradable or biodegradable and osteoactive materials, such as calcium orthophosphates, bone cement, have proved to be promising alternatives for the treatment of osteomyelitis [5]. These systems allow local delivery of the antibiotic in situ with bactericidal concentrations for long periods of time and without the toxicity associated with other means of administration [6].…”
Section: Introductionmentioning
confidence: 99%